Breastfeeding and Opiate Substitution Therapy: Starting to Understand Infant Feeding Choices - Lisa E. Graves; Suzanne Turner; Maya Nader; Sucheta Sinha (SAGE Publishing, 2016)
Introduction Despite research demonstrating the safety and benefit of breastfeeding in opioid substitution therapy, few women in treatment breastfeed. Understanding the factors contributing to the choices women on opioid substitution therapy make about infant feeding is important. Objectives The aim of this study was to better understand and support infant feeding choices and breastfeeding experiences in women on opioid substitution therapy. Methods A systematic review was conducted on five databases: (1) Ovid MEDLINE(R) without revisions, (2) Ovid MEDLINE(R) In-Process & Other Non-Indexed Citations, (3) EMBASE, (4) CINAHL, and (5) FRANCIS. From 1081 articles, 46 articles were reviewed. Results The literature supports breastfeeding as an appropriate and safe option for women on opioid substitution treatment. Breastfeeding and rooming-in reduce neonatal abstinence. Women face barriers to breastfeeding due to societal stigma and the lack of patient and health-care provider education. Conclusions Efforts are needed to increase the knowledge that women and health-care professionals have about the safety and benefits of breastfeeding.